Characterisation of sustainable building walls made from rice straw bales. (March 2020) - Marques, Beatriz; Tadeu, António; Almeida, João; António, Julieta; de Brito, Jorge
Abstract: This study assesses the performance of sustainable building walls made from 80 kg/m 3 and 100 kg/m 3 straw bales. Experimental tests based on the procedures set out in conventional testing guidelines were designed to evaluate their hygrothermal and acoustic characteristics. First, experimental tests were performed to characterise intrinsic properties of rice straw fibres as loose material, such as specific heat capacity, hygroscopic sorption properties and biological resistance. Straw bales were then studied as a building material in terms of thermal conductivity, water vapour permeability and water absorption. The acoustic performance was also assessed by evaluating the airflow resistivity. Finally, different constructive solutions for walls that combined rice straw bales and a variety of coatings (lime mortar, gypsum plaster board and OSB) were studied in terms of thermal transmittance and thermal delay, and with respect to airborne sound insulation. Based on the experimental results presented herein, it can be concluded that rice straw bales can be used to build high performance sustainable building walls. These results also contribute to make the construction industry more confident that such an unconventional building solution can be safely used. Highlights: Experimental tests on two typical rice straw bale densities were performed. Tests on rice straw fibres confirmed their energy storage potential. Thermal conductivity results showed little variation with increasing density. The effect of density was notable for water vapour and water absorption properties. Acoustic performance was improved by using lime mortar as coating wall solutions.